2016
DOI: 10.1016/j.envint.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of perfluoroalkyl substances exposure in utero with reproductive hormone levels in cord blood in the Hokkaido Study on Environment and Children's Health

Abstract: These results suggest that the fetal synthesis and secretion of reproductive hormones may be affected by in utero exposure to measurable levels of PFOS and PFOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 54 publications
4
49
1
Order By: Relevance
“…In addition, we reported that prenatal exposure to PFOS was inversely associated with progesterone levels in cord blood of male and female infants in the same cohort. In contrast, prenatal PFOA levels were positively associated with cord blood progesterone levels in male and female infants (Itoh et al 2016). Therefore, this may partly explain the negative association of PFOS but not PFOA with glucocorticoids in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, we reported that prenatal exposure to PFOS was inversely associated with progesterone levels in cord blood of male and female infants in the same cohort. In contrast, prenatal PFOA levels were positively associated with cord blood progesterone levels in male and female infants (Itoh et al 2016). Therefore, this may partly explain the negative association of PFOS but not PFOA with glucocorticoids in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Previously, our group has reported a negative association between prenatal PFOS and progesterone hormone levels of cord blood samples in male and female infants. In addition, PFOS was negatively associated with testosterone/estradiol in male infants, whereas prenatal PFOA exposure was positively associated with progesterone levels in cord blood samples of both sexes (Itoh et al 2016). However, the effects of PFCs on glucocorticoid hormones and androgenic hormones (the main substrates of testosterone and estrogen) are not well understood in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding metabolic effects, strong inverse associations between maternal PFOS with triglycerides, essential fatty acids and omega 3 and 6 fatty acids during pregnancy have been described [33]. Studies also found that prenatal exposure to PFASs is associated with glucocorticoids (cortisol and cortisone) and reproductive hormone (DHEA, progesterone, estradiol and testosterone) levels [97•, 98], suggesting that PFASs may reprogram the endocrine system and shift steroidogenesis. Mechanisms potentially involved in the neurobehavioral effects of PFASs exposures include influences on calcium homeostasis, protein kinase C, synaptic plasticity, cellular differentiation or via the thyroid hormone system [17, 24, 99].…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiologic evidence does not support a causal association between PFOS exposure and cancer risk in humans 5 . Nonetheless, in utero exposure to PFOS adversely affect the fetal synthesis and secretion of reproductive hormones (e.g., testosterone, estradiol, and inhibin B) in humans 6 . Since the half-life of PFOS and its related compound PFOA (perfluorooctanoic acid) is relatively long, at 5.4-yr and 3.8-yr, respectively 7, 8 , even low-dose exposure to PFOS and its related compounds can accumulate in the body over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%